An adaptive GM-C filter based post-equalizer for wide-band visible light communication systems - Haydar, Emrah. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2022., 2022)
Visible Light Communication (VLC), more commonly known as Li-Fi (Light Fidelity), has been a buzzword since it was first introduced by Harald Haas in 2011. The idea is that a light source can be used as both illumination and communication means. By switching the current of an LED at high speed, data transmission can be performed and the human eye is not disturbed by the flickering. With the recent research in this field, benefits, challenges, and proven solutions have been addressed. One of the big challenges is the limited modulation bandwidth of the transmitter LED which predominantly determines the achievable maximum data rate. Literature review shows that for the white LEDs, the modulation bandwidth is in the range of hundreds of kHz and a few MHz. Methods to extend the modulation bandwidth includes using: coding/modulation schemes, pre- equalizer, lenses/filters, and post equalizers. Among them, a post equalizer is most easily implemented as it deals with small signals at the receiver side. It can be realized with basic or active RC networks and as well as with ANNs as recent works show. In this work, a Gm-C filter-based post equalizer topology has been proposed. By employing 3-bit capacitors, the equalizer can provide eight distinct edge frequencies which correspond to modulation bandwidths of LEDs in the range of 0.7MHz to 5MHz and at least tenfold equalization is achieved. The circuit is realized by using 130nm low threshold MOSFETs and consumes only 240µW. The overall chip area is 340×340µm2 . Post layout simulations, with eye diagrams, show that data rate up to 200MBits is achievable given that a 5MHz modulation bandwidth is available at the receiver side.
Keywords: Optical communications.; Wireless communication systems.; Mining engineering.